2008
DOI: 10.1245/s10434-008-9975-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and Functional Outcome of Scapular Chondrosarcoma

Abstract: Patients with primary chondrosarcoma of the scapula have an excellent oncologic prognosis with a very low local recurrence and metastatic rate. Functional outcomes are better for patients undergoing partial rather than total scapulectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Several surgical treatment types are available, such as total scapulectomy, constrained prosthesis and scapular allograft. All of these surgical treatment options result in very little or no shoulder function (2) , (4) , (5) , (6) , (7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surgical treatment types are available, such as total scapulectomy, constrained prosthesis and scapular allograft. All of these surgical treatment options result in very little or no shoulder function (2) , (4) , (5) , (6) , (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Types of cancer affecting the scapula described in literature are chondro sarcoma, synovial sarcoma, Ewing sarcoma (ES) and metastasis (4) , (5) , (6) , (7) , (16) , (17) . Modern treatment of ES of bone in children and adults consists of chemotherapy and local treatment by surgery or radiotherapy or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Griffin AM et al reported sixteen patients who underwent partial scapulectomy while eight underwent total scapulectomy. Functional outcome was better in the group undergoing partial scapulectomy with significantly higher score than the total scapulectomy group [20]. Kiss J et al also found the best results were achieved after partial scapulectomy, and after humeral resection reconstructed with fibular transposition and with preservation of the rotator cuff [21].…”
Section: Discussionmentioning
confidence: 94%
“…A few studies of total scapulectomy have been published, each of which only contain a small number of cases (Table ). In a study of 13 patients with malignant tumors and a mean follow‐up of 44 months, total scapulectomy followed by humeral suspension was considered to be preferable to forequarter amputation, endoprosthetic reconstruction and allografting.…”
Section: Discussionmentioning
confidence: 99%